Major Vault Protein (MVP) Associated With BRAFV600E Mutation Is an Immune Microenvironment-Related Biomarker Promoting the Progression of Papillary Thyroid Cancer via MAPK/ERK and PI3K/AKT Pathways - Dong, Xubin; Akuetteh, Percy David Papa; Song, Jingjing; Ni, Chao; Jin, Cong; Li, Huihui; Jiang, Wenjie; Si, Yuhao; Zhang, Xiaohua; Zhang, Qiyu; Huang, Guanli (Frontiers in Cell and Developmental Biology, 2022)
Papillary thyroid cancer (PTC) is the most common malignancy of the endocrine system, with an increase in incidence frequency. Major vault protein (MVP) is the main structural protein of the vault complex that has already been investigated in specific cancers. Yet the underlying biological functions and molecular mechanisms of MVP in PTC still remain considerably uncharacterized. Comprehensive analyses are predicated on several public datasets and local RNA-Seq cohort. Clinically, we found that MVP was upregulated in human PTC than in non-cancerous thyroid tissue and was correlated with vital clinicopathological parameters in PTC patients. MVP expression was associated with BRAFV600E, RAS, TERT, and RET status, and it was correlated with worse progression-free survival in PTC patients. Functionally, enrichment analysis provided new clues for the close relationship between MVP with cancer-related signaling pathways and the immune microenvironment in PTC. In PTC with high MVP expression, we found CD8+ T cells, regulatory T cells, and follicular helper T cells have a higher infiltration level. Intriguingly, MVP expression was positively correlated with multiple distinct phases of the anti-cancer immunity cycle. MVP knockdown significantly suppressed cell viability and colony formation, and promoted apoptosis. In addition, downregulated MVP markedly inhibited the migration and invasion potential of PTC cells. The rescue experiments showed that MVP could reverse the level of cell survival and migration. Mechanistically, MVP exerts its oncogenic function in PTC cells through activating PI3K/AKT/mTOR and MAPK/ERK pathways. These results point out that MVP is a reliable biomarker related to the immune microenvironment and provide a basis for elucidating the oncogenic roles of MVP in PTC progression.